Involvement of MMP‐9 in collagen degradation of sea bass (Lateolabrax japonicus): Cloning, expression, and characterization. Issue 2 (28th December 2022) - Yang, Ru‐Qing; Chen, Yu‐Lei; Sun, Le‐Chang; Ou, Wei; Liu, Hai‐Yan; Zhang, Ling‐Jing; Liu, Guang‐Ming; Zhao, Guanghua; Cao, Min‐Jie
Abstract : Abstract: Disintegration of intramuscular connective tissue is responsible for postmortem tenderization of fish muscles during chilled storage. Matrix metalloproteinase‐9 (MMP‐9) was reported to be involved in this process, whereas the mechanism has not been revealed. In the present study, purified type I and V collagens from the connective tissues of sea bass ( Lateolabrax japonicus ) muscles were first prepared. These two kinds of collagens comprise three polypeptide chains (α), forming a typical triple‐helical domain as determined by circular dichroism. The complete coding region of MMP‐9 containing an open reading frame of 2070 bp encoding 689 amino acid residues was then cloned. The recombinant MMP‐9 catalytic domain (rcMMP‐9) was expressed in Escherichia coli and exhibited high hydrolyzing activity toward gelatin. Besides, rcMMP‐9 was effective in degrading type V collagen rather than type I collagen at 4°C. The enzymatic activity of rcMMP‐9 was highly pH‐dependent, and its enzymatic activity under neutral and basic conditions was higher than that under acidic conditions. Metal ion Ca 2+ was necessary for the maintenance of rcMMP‐9 activity, whereas Zn 2+ inhibited its activity. Our present study indicated that MMP‐9 is responsible for the disintegration of intramuscular connective tissues by cleaving type V collagen during postmortem tenderization of fish muscle. Practical Application: Elucidation the involvement of MMP‐9 in collagen degradation will deliver a reference for the prevention of muscular protein decomposition during chilled storage of fish fillets.